Oxidative balance score reflects vascular endothelial function of Chinese community dwellers - Liu, Jianhua; He, Lingxiao; Wang, Aozhe; Lv, Yuanyuan; He, Hui; Wang, Chenghao; Xiong, Kaiyu; Zhao, Li (Frontiers in Physiology, 2023)
Background: The oxidative balance score (OBS) is a composite estimate of the overall pro- and antioxidant risk status in an individual. The aim of this study was to explore the association between OBS and vascular endothelial function in Chinese community dwellers. Methods: 339 community dwelling adults (aged 20-75 years) were recruited in this study. Overall OBS was calculated based on 16 pro- and antioxidant factors related to diet (measured by fasting blood samples) and lifestyle (evaluated by questionnaires). Dietary OBS and Lifestyle OBS were calculated based on corresponding components. Serum iso-prostaglandin F2α (FIP) was measured to evaluate oxidative stress degree and brachial artery blood flow-mediated dilation (FMD) was measured for vascular endothelial function. FIP and FMD levels were dichotomized as “low” or “high” using corresponding median values (Low FIP, n=159; High FIP, n=180; Low FMD, n=192; High FMD, n=147). Components of OBS were compared between stratified FIP and FMD groups. Logistic regression was used to analyze OBS associations with FIP and FMD. Results: Higher Overall OBS and Dietary OBS were associated with lower FIP (P<0.001). On the other hand, higher overall OBS (P<0.01) and dietary OBS (P<0.05) were associated with higher FMD. Lifestyle OBS was not associated with FIP and FMD (P>0.05). Except for body mass index BMI and low physical activity all other OBS components were significantly different between Low FIP and High FIP groups (P<0.05). Four diet-related antioxidants (α-carotene, zeaxanthin, α-tocopherol, and γ-tocopherol) showed significant differences between high and low FMD groups (P<0.05). Conclusions: Decreasing OBS level was associated with low endothelial function and high oxidative stress. Dietary OBS, rather than lifestyle OBS, was more closely associated with endothelial function.